A Structural Landscape of Neutralizing Antibodies Against SARS-CoV-2 Receptor Binding Domain - Niu, Ling; Wittrock, Kathryn N.; Clabaugh, Gage C.; Srivastava, Vikram; Cho, Michael W. (Frontiers in Immunology, 2021)
SARS-CoV-2, a novel coronavirus responsible for the ongoing COVID-19 pandemic, has been spreading rampantly. The global scientific community has responded rapidly to understand immune correlates of protection to develop vaccines and immunotherapeutics against the virus. The major goal of this mini review is to summarize current understanding of the structural landscape of neutralizing antibodies (nAbs) that target the receptor binding domain (RBD) of viral spike (S) glycoprotein. The RBD plays a critical role in the very first step of the virus life cycle. Better understanding of where and how nAbs bind the RBD should enable identification of sites of vulnerability and facilitate better vaccine design and formulation of immunotherapeutics. Towards this goal, we compiled 38 RBD-binding nAbs with known structures. Review of these nAb structures showed that (1) nAbs can be divided into five general clusters, (2) there are distinct non-neutralizing faces on the RBD, and (3) maximum of potentially four nAbs could bind the RBD simultaneously. Since most of these nAbs were isolated from virus-infected patients, additional analyses of vaccine-induced nAbs could facilitate development of improved vaccines.